ADVERSITY INTELLIGENCE VIEWED FROM HIGHLOW SOCIAL SUPPORT IN DAAR ELQOLAM JAYANTI ISLAMIC BOARDING SCHOOL STUDENTS, TANGERANG, INDONESIA - Asmi Rozali, Yuli; M. , Fahad Sya'Bana; Safitri,; Faritzal, Adam (International Journal of Psychosocial Rehabilitation, 2020)
New students in boarding school feel the differences between their home school environment and conditions environment. These make the student must be able to adapt with the new environment and academic demands. Students are required to quickly adapt to the new environment, managing their time between studying, playing and subject memorizing. Adversity intelligence is something that students need when facing and dealing with their problems. One of the factor affecting adversity intelligence is the social support. The purpose of this research is to determine the effect of social support on adversity intelligence in students of Daar el-Qolam Islamic Boarding School. The design of this research is comparative causal with a simple random sampling technique with 219 sample students of Daar el Qolam Boarding School. Social support measurements are using scale of social support with a magnitude of reliability (α) = 0.936 with 52 valid items. Adversity intelligence measurement is using the item scale of adversity intelligence with reliability (α) = 0.886 with 36 valid items. Based on the results of the chi square test, this research earned sig score (p) = 0.045; ((p)